2015
DOI: 10.1016/j.seppur.2015.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Evidencing the chemical degradation of a hydrophilised PES ultrafiltration membrane despite protein fouling

Abstract: Hydrophilisation of polyethersulfone (PES) based membrane is often achieved by addition of polyvinylpyrrolidone (PVP) leading to a physical blend of the two polymers. This paper shows that the most commonly used membrane for UF in dairy industry is a PES/PVP based one. Nevertheless if hydrophilisation limits the organic fouling, PVP is also the Achilles heel of these membranes. It is particularly true when membranes are exposed to hypochlorite as it is the case for cleaning/disinfection steps. Evidencing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…Since no cation was detected along with chlorine it was concluded that chlorine was most probably covalently bonded to the membrane backbone and not adsorbed in a salt form (i.e. Cl -together with a charge-balancing cation) [10,23]. Such an observation was in good agreement with further investigations carried out by Hanafi et al who used XPS to show the existence of C-Cl bonds on aged membranes while no chlorine was observed on pristine membrane surfaces [14].…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Since no cation was detected along with chlorine it was concluded that chlorine was most probably covalently bonded to the membrane backbone and not adsorbed in a salt form (i.e. Cl -together with a charge-balancing cation) [10,23]. Such an observation was in good agreement with further investigations carried out by Hanafi et al who used XPS to show the existence of C-Cl bonds on aged membranes while no chlorine was observed on pristine membrane surfaces [14].…”
Section: Introductionsupporting
confidence: 76%
“…In more drastic ageing conditions dislodgement of PVP from the membrane matrix has even been reported [3,10,13,15,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, membrane mechanism has been widely utilized for water and wastewater treatment [2,3], gas separation [4], food and beverage processing [5], and in the pharmaceutical industry for enzyme and protein concentration [6], Membrane technology offers better control of the treatment rate and product quality, thereby making it very attractive for replacing conventional separation technology, when applicable. In industrial applications, manufacturers select membranes that have good mechanical properties, high permeability, and selectivity, and that are capable of being applied at high temperatures, with resistance to extreme chemical solutions, and low fouling tendency.…”
Section: Introductionmentioning
confidence: 99%